FORENSIC TAPHONOMY OF MASS GRAVES - Vaduveskovic, Igor (Medicinski podmladak, 2024)
When it comes to mass graves, especially secondary ones (moved from the primary location), due to the high fragmentation of the body, the archaeological context is much more complex, which complicates the process of exhumation, analysis and interpretation of data, and requires statistical data processing. The intensity of fragmentation of human remains differs between graves depending on the formation processes of the grave and/or peri-mortem (at the time of death or near it) circumstances related to the individuals in it. Ssubject of this paper is an overview of the methods of analyzing the taphonomic imprint that such processes form over time on human remains as well as the presentation of the process of degradation of the human body in the context of mass graves.
Keywords: taphonomy; decomposition of bodies, post mortem interval, mass graves, fragmentation